Identification of genomic regions of wheat associated with grain Fe and Zn content under drought and heat stress using genome-wide association study - Devate, Narayana Bhat; Krishna, Hari; Sunilkumar, V. P.; Manjunath, Karthik Kumar; Mishra, C. N.; Jain, Neelu; Singh, G. P.; Singh, P. K. (Frontiers in Genetics, 2022)
Abstract: Wheat is the staple food crop of global importance for its grain nutrient quality. Grain iron and zinc content of wheat grain is an important quantitatively inherited trait which is influenced by the environment such as drought and heat stress. Phenotypic evaluation of 295 advanced breeding lines from wheat stress breeding program of IARI was done under timely sown irrigated (IR), restricted irrigated and late sown conditions at New Delhi during cropping season of 2020-21 and grain iron (GFeC) and Zinc (GZnC) contents were estimated from both control and treatments. Statistically significant increase in GFeC and GZnC was observed under stress conditions compared to control. Genotyping was done with the SNPs from 35K Axiom Breeder’s Array and marker trait association was identified by GWAS analysis. Out of 23 MTAs identified, seven were linked with GFeC and sixteen were linked with GZnC. Insilico analysis revealed few important transcripts involved in various plant metabolism, growth and development activities such as Auxin response factor, Root UVB sensitive proteins, Potassium transporter, Glycosyl transferase, COBRA, F-box-like domain etc. The identified MTAs can be used for molecular breeding after validation and can be utilized for rapid development of micronutrient rich varieties of wheat to mitigate hidden hunger